Independent association of PD‐L1 expression with noninactivated VHL clear cell renal cell carcinoma—A finding with therapeutic potential. Issue 1 (23rd September 2016) - Kammerer‐Jacquet, Solène‐Florence; Crouzet, Laurence; Brunot, Angélique; Dagher, Julien; Pladys, Adélaïde; Edeline, Julien; Laguerre, Brigitte; Peyronnet, Benoit; Mathieu, Romain; Verhoest, Grégory; Patard, Jean‐Jacques; Lespagnol, Alexandra; et al.
Abstract : Clear cell renal cell carcinoma (ccRCC) is an aggressive tumor that is characterized in most cases by inactivation of the tumor suppressor gene VHL . The VHL/HIF/VEGF pathway thus plays a major role in angiogenesis and is currently targeted by anti‐angiogenic therapy. The emergence of resistance is leading to the use of targeted immunotherapy against immune checkpoint PD1/PDL1 that restores antitumor immune response. The correlation between VHL status and PD‐L1 expression has been little investigated. In this study, we retrospectively reviewed 98 consecutive cases of ccRCC and correlated PD‐L1 expression by immunohistochemistry (IHC) with clinical data (up to 10‐year follow‐up), pathological criteria, VEGF, PAR‐3, CAIX and PD‐1 expressions by IHC and complete VHL status (deletion, mutation and promoter hypermethylation). PD‐L1 expression was observed in 69 ccRCC (70.4%) and the corresponding patients had a worse prognosis, with a median specific survival of 52 months ( p = 0.03). PD‐L1 expression was significantly associated with poor prognostic factors such as a higher ISUP nucleolar grade ( p = 0.01), metastases at diagnosis ( p = 0.01), a sarcomatoid component ( p = 0.04), overexpression of VEGF ( p = 0.006), and cytoplasmic PAR‐3 expression ( p = 0.01). PD‐L1 expression was also associated with dense PD‐1 expression ( p = 0.007) and with ccRCC with 0 or 1 alteration(s) (non‐inactivated VHL tumors; p = 0.007) that remained significant after multivariate analysis ( p = 0.004 and p = 0.024, respectively). Interestingly, all wild‐type VHL tumors (no VHL gene alteration, 11.2%) expressed PD‐L1. In this study, we found PD‐L1 expression to be associated with noninactivated VHL tumors and in particular wild‐type VHL ccRCC, which may benefit from therapies inhibiting PD‐L1/PD‐1. Abstract : What's new? Programmed death‐ligand 1 (PD‐L1) is aberrantly expressed in clear cell renal cell carcinoma (ccRCC), making it a key target for new immunotherapeutic agents. In general, such therapies are administered when tumors become resistant to agents that block angiogenic processes fueled by inactivation of the tumor suppressor gene VHL, a feature common to most ccRCCs. Here, in ccRCC samples from patients who underwent radical nephrectomy, PD‐L1 expression was found to be associated with non‐inactivated or wild‐type VHL ccRCC but not inactivated VHL disease. Moreover, patients with wild‐type VHL ccRCC and PD‐L1 expression exhibited relatively worse prognosis.